Phosphorylation of CalDAG‐GEFI by protein kinase A prevents Rap1b activation. Issue 8 (14th August 2013) - Subramanian, H.; Zahedi, R. P.; Sickmann, A.; Walter, U.; Gambaryan, S.
Summary Background Signaling via protein kinase A (PKA) and protein kinase G (PKG) is critical for maintaining platelets in the resting state. Both kinases down‐regulate the activity of the small GTPase Rap1b, a critical signaling switch for integrin activation and platelet aggregation. However, the mechanism of Rap1b regulation by PKA and PKG is largely unknown. Objective To identify the PKA phosphorylation sites in calcium and diacylglycerol‐regulated guanine nucleotide exchange factor I (CalDAG‐GEFI), the main GEF for Rap1b in platelets, and the effect of CalDAG‐GEFI phosphorylation in Rap1b activation. Methods The phosphorylation sites in CalDAG‐GEFI were identified by radio‐active phosphate incorporation assay and mass spectrometry. Phospho‐antibody was developed to detect CalDAG‐GEFI phosphorylation in Western blots. Rap1b activation was detected by Rap1‐GTP pull‐down assay. Results S587 was identified as the major PKA phosphorylation site in CalDAG‐GEFI, while S116/117 was weakly phosphorylated. Phosphorylation of S587 correlated with the inhibitory effect of PKA on Rap1b activation in platelets. In HEK293 cells, expression of a phospho‐mimetic mutant of CalDAG‐GEFI (S587D) abolished agonist‐induced Rap1b activation. Mutation of S587 to alanine partially reversed the inhibitory effect of PKA signaling on Rap1b activation, while mutation of S116, S117 and S587 to alanine completely abolished the inhibitory effect of PKA on Rap1b activation. Conclusion Our study strongly suggests that phosphorylation of CalDAG‐GEFI is a critical mechanism by which PKA controls Rap1b‐dependent platelet aggregation.